2015
DOI: 10.1523/jneurosci.4203-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Macaque Superior Temporal Sulcus: Functional Delineation of Vergence and Version Eye-Movement-Related Activity

Abstract: It is currently thought that the primate oculomotor system has evolved distinct but interrelated subsystems to generate different types of visually guided eye movements (e.g., saccades/smooth pursuit/vergence). Although progress has been made in elucidating the neural basis of these movement types, no study to date has investigated all three movement types on a large scale and within the same animals. Here, we used fMRI in rhesus macaque monkeys to map the superior temporal sulcus (STS) for BOLD modulation ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…By combining fMRI with and without SC inactivation, we found that the same fSTS region exhibited the largest reduction in attention-related BOLD modulation during the attention deficits caused by SC inactivation (figure 1d; 8 ). Relatively little is known about this cortical fSTS region 9-14 and it is unclear why it emerged in fMRI as the primary cortical area dependent on SC activity during the attention task. Our next step was to target this region for extracellular recording (figure 1e) to identify the signals conveyed by neurons and how these signals might depend on superior colliculus activity.…”
Section: Main Textmentioning
confidence: 99%
“…By combining fMRI with and without SC inactivation, we found that the same fSTS region exhibited the largest reduction in attention-related BOLD modulation during the attention deficits caused by SC inactivation (figure 1d; 8 ). Relatively little is known about this cortical fSTS region 9-14 and it is unclear why it emerged in fMRI as the primary cortical area dependent on SC activity during the attention task. Our next step was to target this region for extracellular recording (figure 1e) to identify the signals conveyed by neurons and how these signals might depend on superior colliculus activity.…”
Section: Main Textmentioning
confidence: 99%
“…Finally, we used the detected saccades as regressors of non-interest in our GLM. It is also worth noting that the activations we observed when contrasting our two conditions of interest (CSM vs. TS) are different from the vergence networks as investigated in terms of vergence tracking and vergence steps by Ward and collaborators (Ward et al 2015). Additional analyses based on fixation performances and variance of eye position along the x and y axes during the CSM and TS conditions further demonstrated that eye movements did not impact our results (see supplementary figure 2 and the accompanying text).…”
Section: Discussionmentioning
confidence: 47%
“…Note that with increasing blur levels the contrast of the stimuli decreased. The blur levels employed can be equated to contrast levels of [100,95,78,59,48,35,20] In the binocular blur trials, the stimuli presented to both eyes were blurred. In the monocular blur trials, only the stimuli shown to the left eye were blurred, whereas a sharply focused stimulus was always shown to the right eye.…”
Section: Stimulimentioning
confidence: 99%
“…The cerebellum, which is directly involved in the control of both pursuit [103,92] and vergence [27,26] eye movements, likely plays an important role in the synchronization of the oculomotor and arm motor systems [61,62]. If the same synchronization signals from the cerebellum were to converge onto separate vergence and pursuit-specific neural loci [25,100], these signals might differentially impact oculomotor tracking performance in depth and along the frontal plane.…”
Section: Mechanisms Of Eye-hand Coordinationmentioning
confidence: 99%
See 1 more Smart Citation